Narrowband Imaging of a z = 3.24 Protocluster: Insights from [O iii]-emitting Galaxies - Ke Shi; Jun Toshikawa; Xianzhong Zheng; Zheng Cai; Dongdong Shi (The Astrophysical Journal)
We present narrowband imaging of a spectroscopically confirmed protocluster “D4UD01” at z = 3.24 using CFHT/WIRCam. We identify a sample of 24 [O iii ] emission-line galaxies in the field, which forms a large overdensity in the protocluster region. The protocluster is expected to evolve into a Virgo-like cluster by z = 0. Utilizing multiwavelength data, we derive the physical properties of these [O iii ] emitters and find that they are intermediate-mass normal star-forming galaxies (∼10 ^10 M _⊙ ) roughly following the star-forming main sequence. The [O iii ] emitters trace an overdensity spatially offset from that of photometric-redshift and quiescent galaxies, suggesting that these distinct galaxy populations may inhabit dark matter halos that formed at different epochs. A comparative analysis of [O iii ]-emitter properties shows similar characteristics in both protocluster and field environments. This protocluster likely represents an evolved structure that has progressed beyond its peak star formation phase, although our limited sample size may prevent detection of subtle environmental effects.